(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
In this article, we investigate streaming Russian-Uzbek machine translation under dense, spontaneous code-switching. We propose a latency-controlled Transformer that combines wait-k scheduling with monotonic chunkwise attention, augmented by script and morphology-aware tokenization and a boundary-sensitive read/write policy. On chat-style test sets, the system delivers higher BLEU and chrF at the same Average Lagging and better preserves switch points and Russian stems bearing Uzbek suffixes.